Efecto de los polifenoles del extracto de amaranto negro (Amaranthus hybridus L.), sobre la actividad antioxidante y vida útil del chorizo - Freire Chamorro, Edison Alexander (2023)
The objective of this research project is to determine the effect of polyphenols present in the extract of black amaranth (Amaranthus hybridus L.) on the antioxidant activity and shelf life of chorizo. A freeze-dried extract was made by maceration with agitation, where the total polyphenols were identified by the Folin Ciocalteu method and the antioxidant capacity was quantified by the 2.2-diphenyl- 1-picrylhydrazyl (DPPH) method. To determine the effect of the polyphenols of this extract, four chorizos treatments were prepared, one control and three with different percentages of addition thereof, which were: 0,1 %, 0,3 % and 0,5 %. The determination of the shelf life of this product was carried out through reaction kinetics, determination of the presence of Salmonella and total coliform count. In addition, through physicochemical and microbiological tests, the pH, fat, protein and water retention capacity were determined, to establish the compliance of the product with the INEN 1338:2012 standard, on the other hand, the level of acceptability was determined through tasting tests where their organoleptic characteristics were evaluated. Through the results of the tests carried out, it was possible to determine that the optimal concentration of the addition of the natural extract of black amaranth (Amaranthus hybridus L.) as a natural antioxidant was the treatment with 0,5 %, as it was the treatment with the highest antioxidant capacity, less microbial load, stability in organoleptic properties and the longest shelf life.